Uncomfortable neighbors: NATO, Russia and the shifting logic of military exercises in the Baltics. Issue 1 (2nd January 2023) - Banka, Andris; Bussmann, Margit
ABSTRACT: To what ends do allies employ military exercises? In order to further our understanding regarding the logic and utility of military drills, this paper focuses on NATO's eastern flank. Specifically, with the help of newly compiled data, we tracked two decades of exercises in the Baltic states. Our analysis speaks to the fact that the size, tempo, and character of military training events in this region have manifestly changed. In the early 2000s, military drills were primarily conceived as a mechanism to modernize Baltic armed forces and ensure their adequacy to NATO membership standards. The 2014 Crimea crises, however, dealt a serious blow to the regional order. This event was the primary driver behind a considerable spike in the overall exercise numbers. At the same time, we observe that it was not only a mere quantitative shift that transpired. From parachute drops into remote areas, rehearsals of river crossings to moving of combat power via narrow land corridors, the staging of military exercises after 2014 were overhauled into events that accentuated NATO's reinforcement capabilities. In this context, military exercises can be seen as a crucial element to credibly signal capacity and resolve within the concept of deterrence by reinforcement.